Knowledge on American Heart Association Guidelines Update for Cardiopulmonary Resuscitation among the Nurses Working at University Hospital, Kavre - Shrestha, S.; Shrestha, R.; Karmacharya, R.M.; Ranjit, S. (Kathmandu University Medical Journal, 2020)
Background Cardiopulmonary resuscitation is the foundational technique for the emergency treatment of cardiac arrest and the standardized training of it has been emphasized more than ever. Competence of the nurses in this lifesaving procedure is a critical factor in patient outcome from cardiac arrest and can largely prevent sudden death.Objective Many evidences suggest lack of knowledge on proper cardiopulmonary resuscitation among nurses so the aim of this study was to assess the knowledge on 2015 American Heart Association guidelines update for cardiopulmonary resuscitation among nurses working at University hospital and to identify the relationship between the level of knowledge and selected variables.Method Two hundred and sixty nurses working in Dhulikhel hospital participated in the study. A cross-sectional descriptive study was conducted using a predesigned questionnaire based on 2015 guidelines updates for cardiopulmonary resuscitation that incorporated total of 20 questions.Result Total 260 participated in the study and all were female. Only one third of the nurses had good knowledge regarding 2015 guidelines update for cardiopulmonary resuscitation. No significant results existed between the knowledge score and age of the nurses, duration of work experience. However, significant results existed between the knowledge score and qualification, designation of the nurses and previous training on cardiopulmonary resuscitation.Conclusion One third of the nurses had good knowledge regarding 2015 guidelines update for cardiopulmonary resuscitation in this study. Thus, knowledge and practical approach has to be updated with current guidelines in cardiopulmonary resuscitation in order to improve the safety and effectiveness of patient care.